1960
DOI: 10.1038/bjc.1960.73
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Induction of Breast Tumours in the Rat: Hormonal Factors in Tumour Production

J S Howell

Abstract: MAMMARY tumours in the rat can be induced by a variety of methods. These include intensive treatment with hormone preparations, e.g. growth hormone (Moon et al., 1950) and oestrogens (Geschickter, 1939; Mackenzie, 1955), by the administration of aminofluorene compounds (Bielschowsky, 1944(Bielschowsky, , 1947 Symeonidis, 1954) and by certain carcinogenic hydrocarbons. These latter substances have been administered by various routes, but the most rapid method of induction has been reported by Huggins, Briziare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1962
1962
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The study was conducted in seven areas of the world, included populations that exhibited a wide range of incidence rates for breast cancer, and involved 4323 cases and 12,699 controls. Others observed that parity provided significant protection from chemically induced mammary cancer in rats (Howell 1960, Moon 1969, Moore et al 1981. We found that GH was significantly lower in parous rats compared with age-matched virgin controls, while other mammotropic hormones were not significantly altered (Thordarson et al 1995).…”
Section: Mammary Cancersupporting
confidence: 40%
“…The study was conducted in seven areas of the world, included populations that exhibited a wide range of incidence rates for breast cancer, and involved 4323 cases and 12,699 controls. Others observed that parity provided significant protection from chemically induced mammary cancer in rats (Howell 1960, Moon 1969, Moore et al 1981. We found that GH was significantly lower in parous rats compared with age-matched virgin controls, while other mammotropic hormones were not significantly altered (Thordarson et al 1995).…”
Section: Mammary Cancersupporting
confidence: 40%
“…Other chemical inducers of tumours include the administration of high doses of growth hormones, oestrogens or aminofluorene compounds that stimulate the development of mammary tumours [8]. These chemical inducers are toxic and harmful to the animal upon administration and offers low tumour development or growth rates that may take up to 3-4 months before the appearance of an external tumour growth [9].…”
Section: Introductionmentioning
confidence: 99%